Determinants of lamikro adoption among micro and small businesses: a technology acceptance model (TAM) approach - Nurhayati; Nopi Hernawati; Dewi Rahmi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
From a sharia economic perspective, Indonesia, with its Muslim majority population, has great potential to develop a halal/sharia ecosystem that encompasses various sectors such as food, tourism, fashion, cosmetics, and finance. The sustainability of this ecosystem also has implications for the Micro, Small, and Medium Enterprises (MSME) sector. In the digital age, challenges include the low capacity of MSMEs in business management, financial reporting, technological limitations, and non-compliance with financial and Islamic standards. A total of 33 MSMEs have been able to upload financial data to the Lamikro application, read and analyze financial reports, and understand the concept of Islamic accounting. The objective of this activity is to assist in resolving these issues through mentoring and training for MSMEs in preparing financial reports using the Lamikro application. By using the Lamikro app to create financial reports, SMEs can manage and report their finances more effectively and efficiently, ensuring transparency and reliability, evaluate product performance, manage cash flow and liquidity more easily, and communicate with investors for Muslim Women's Warung SMEs in Cisaranten Kulon Village, Bandung City.